Closing the Gender Gap in Corporate Advancement: Insights and Solutions from Behavioural Economics - Heckbert, Lori Anne (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
Despite evidence that both gender and ethnically diverse leadership is good for businesses’ bottom line, just one in five senior North American business leaders is female, one in thirty a woman of colour. Little literature exists applying behavioural economics [BE] concepts to explain gender gaps. Yet, as demonstrated by the 2010 UK Conservative-Liberal Democrats coalition government, the Obama government in the US and Trudeau government in Canada, lawmakers, policymakers and business leaders are interested in BE’s persuasive power to influence behaviour. My contribution exploits this interest, builds on the excellent existing scholarship analyzing gender gap concepts from a BE perspective, and fills this gap. Applying concepts of bounded rationality, bounded willpower, bounded self-interest, and the endowment effect to 2017’s North American-focused Women in the Workplace report (Report) published by LeanIn and McKinsey, a vast study examining HR practices and pipeline data of 222 companies employing 12 million+ people and surveying 70,000+ employees’ experiences, I find that hiring and promotion decisions are affected by the three bounds and endowment effect, undercutting businesses’ compelling economic interest in diverse leadership. BE offers solutions to tackle biased behaviour and shows how gender gap scholars’ and the Report’s recommendations can be taken further to close the gender gap in advancement. I argue that normative best practice adoption by business and nudges and tax incentives from governments, ideally in combination, can spur businesses to adopt debiasing behaviours and practices that will contribute to closing the gender gap in advancement. Enabling women to achieve their full leadership and economic potential will enhance women’s wellbeing, improve businesses’ performance, and lead to greater social equity.